Increasing Aircraft Carrier Forward Presence : Changing the Length of the Maintenance Cycle. - Yardley, Roland F. (Rand Corporation Monograph., 2008)
The U.S. Navy?s aircraft carriers allow the nation to deter adversaries, bring airpower to bear against opponents, engage friends and allies, and provide humanitarian assistance. However, these powerful and versatile systems need continuous and regularly scheduled maintenance, and their crews require a great deal of training to attain and sustain readiness levels. The length of the carrier?s training, readiness, deployment, and maintenance cycle, the type of maintenance needed, and the timing of events within the cycle affect the carrier?s availability to meet operational needs. Over the past.